GLP-1 Receptor Agonists in the Treatment of Obesity: A Narrative Review of Current Therapeutic Methods - Borkowski, Konrad; Leja, Wiktoria; Błaszczak, Maciej; Latalska, Katarzyna; Szczupaj, Maciej; Januszczak, Radosław; Pastuszak, Andżelika; Rudnicki, Jakub; Zjawiony, Julia; Zulfiqar, Zeeshan (Quality in Sport, 2026)
Introduction. Obesity is now considered to be one of the largest public health challenges of the twenty-first century, with over one billion adults affected. With conventional treatments such as lifestyle modifications and bariatric surgery being either ineffective or unavailable to the majority of obese individuals, there is an urgency for the development of safe and effective pharmacologic therapies. GLP-1 receptor agonists have developed into a unique and highly successful class of drugs that produce clinically relevant weight loss in addition to improving cardiovascular and metabolic risk factors. Aim of the Study. This review aims to provide a practical and inclusive summary of GLP-1 receptor agonist therapy in obesity, focusing on mechanism of action, currently approved agents, clinical effectiveness, safety profiles and next generation therapeutic approaches. Methodology. A literature search was conducted in PubMed/MEDLINE and ClinicalTrials.gov, covering publications from 2015 to March 2026. Randomized controlled trials, systematic reviews, meta-analyses, and expert consensus papers were prioritized. Conclusions. The GLP-1 receptor agonists represent a paradigm shift in the treatment of obesity, achieving weight reductions of up to 21%. Both medications also appear to reduce cardiovascular disease risk in non-diabetic populations. While gastrointestinal side effects are the most commonly reported adverse reactions associated with these medications they can be effectively managed. As with all chronic diseases, once these medications are discontinued, patients will experience weight gain which emphasizes the importance of providing long term treatment options. Next-generation agents, including retatrutide and the cagrilintide-semaglutide combination, show even greater weight-reducing potential. Ensuring equitable access, long-term safety monitoring, and individualized treatment approaches remain the key challenges for the field.